Strategi Manajemen Pendidikan Islam dalam Menghadapi Tantangan Digitalisasi Pendidikan (JMPI: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to examine the strategies of Islamic education management in addressing the challenges of educational digitalization. The research employs a qualitative approach with a literature review design, analyzing relevant scholarly sources published within the last ten years. The findings indicate that digitalization presents both challenges and opportunities, requiring a comprehensive transformation in Islamic education management, including shifts in paradigms, systems, and organizational culture. This transformation encompasses data-driven planning, flexible and collaborative organizational structures, technology-based learning implementation, and comprehensive and continuous evaluation systems. Furthermore, the integration of Islamic values within the digital ecosystem is a crucial aspect in maintaining the balance between technological advancement and character development of learners. Strengthening teachers’ digital competencies is also a key factor, achieved through structured training, continuous learning culture, and adequate system and infrastructure support. However, challenges such as digital literacy gaps and resistance to change remain significant obstacles. Therefore, Islamic education management strategies must be adaptive, integrative, and sustainable to develop an innovative educational system while preserving its Islamic identity. Keywords: Islamic education management, educational digitalization, educational transformation, digital competence, integration of Islamic values